La ciudad de pi - Solís-Palma, Angie (My University, 2022)
En este video se presenta una actividad lúdica utilizando los decimales del número irracional Pi, para representar la silueta de una ciudad.

This video presents a playful activity using the decimals of the irrational number Pi, to represent the silhouette of a city.
Keywords: Pi; Números racionales; Geometría; Matemáticas; Rational numbers; Geometry; Mathematics